Students’ Awareness on Speaking Anxiety in English for Specific Purpose Speaking Project - I Wayan Suadnyana; Muhamad Nova (EDULIA: English Education, Linguistic and Art Journal, 2021)
This study aimed at finding out students’ awareness of speaking anxiety and the type of speaking anxiety occurring in English for the Specific Purpose speaking project. The study employed a qualitative approach with a case study design and used questionnaires and interviews to collect the data. The study was conducted in one vocational school in Denpasar, with a total of 51 students participating. The data were analyzed through data reduction, data display, and conclusion drawing. As a result, it was found that more than half of the students (58.82%) were being aware of their speaking anxiety during the voice recording. The panic attack and feeling worried become the type of anxiety that the students felt. In conclusion, the anxiety arose due to their lack of English language mastery and their fear of listeners’ comments toward their voice recording. Teachers and lecturers are required to support the students and motivate them to practice the language praxis. Keywords: English for Specific Purpose, Speaking Anxiety, Student’s Awareness